Constructing Co-O-P bridging to induce spin state reconfiguration: In situ electro-oxidation of P for industrial-scale alkaline water electrolysis - Miao Ma; Chuan-De Qi; Qiao Xia; Qian-Xi Lv; Xin-Jie Tian; Man-Man Li; Sheng-Jun Xu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2026)

Synergistic TP/APTES coating on PBT membrane enables superhydrophilicity and efficient oil-water separation - Shuiling Hong; Chenyang Li; Xin Wu; Ang Gao; Haoming Duan; Man Liu; Sijia Zhang; Shuo Yang; Leixin Yang; Dengkun Shu; Jingwei Xie; Bowen Cheng (Journal of Environmental Chemical Engineering, 2026)

Endothelial VEGFR2 insufficiency promotes the transition of lymphatic to hematopoietic transcriptional programs - Taotao Li; Xudong Cao; Fei Zhou; Xiujuan Li; Wenjuan Ma; Xiuyan Zhang; Haoyu Zhong; Beibei Xu; Man Chu; Xiwen Jia; Kai Ding; Xin Shen; et al. (Angiogenesis, 2026)

Homothorax regulates BarH1 expression and olfactory perception in Monochamus alternatus hope - Qi-Cheng Li; Sheng-Xin Wu; Mei-Jiao Yang; Pu-Yuan Zhang; Yan-Ling Wei; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Burdock leaf polysaccharide as a clean-label bio-preservative for meat: Structural characterization, multifaceted antibacterial mechanisms, and shelf-life extension efficacy - Yong-xin Li; Chan Zhang; Linchong Hui; Xiangfeng Liu; Yuting Sun; Man Liu; Jun Tian (Food Chemistry, 2026)

Nitrogen-Phosphorus Co-Doped Biochar for Persulfate Activation in Sulfadiazine Degradation: Degradation Performance, Mechanism and Toxicity Assessment - Weiwei Yu; Rongqi Liu; Ting Ai; Yufeng Mao; Jiajie Li; Lu Lv; Dan Liu; Yan Luo; Wang Xin; Man Luo; Boyu Liu (Water, Air, & Soil Pollution, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Contagion in global clean energy markets: Evidence from multilateral and unilateral policy episodes - Cody Yu-Ling Hsiao; Pengyang Li; Chin Man Chui; Xin Zheng (Energy Policy, 2026)

Structural evolution-based ancestral sequence reconstruction of medium-chain alcohol dehydrogenase for efficient synthesis of fused-ring chiral alcohols - Jun Wang; Songyin Zhao; Lehang Li; Manman Zhu; Man Zou; Xin Su; Jie Gu; Yan Xu; Yao Nie (Bioresource Technology, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Cadophorin C, a new cyclic heptapeptide isolated from a mangrove-derived fungus Penicillium sp. GXIMD 03101 - Jia-Li He; Xiao-Dong Jiang; Yu-Man Gan; Xin-Jian Qu; Xiang-Xi Yi; Yong-Hong Liu; Cheng-Hai Gao; Meng Bai (Natural Product Research, 2026)

Point-of-use water treatment: energy-autonomous synergistic solar photothermal-piezocatalysis on MXene/Bi2WO6 membranes for distributed removal of sulfonamide antibiotics - Junzhuo Cai; Jiaxin Liu; Yu Bon Man; Jixiang Chen; Luting Li; Xiaoxun Xu; Chengyi Huang; Changlian Xu; Guochun Lv; Xin Qi; Zhanbiao Yang; Guiying Wang; et al. (Water Research, 2025)

Co-inoculation of Bacillus amyloliquefaciens and Pleurotus ostreatus alleviates replanting obstacles in continuously cropped soil by enhancing the soil nutrient cycle and beneficial microorganisms - Xue Luo; Man Xu; Xin-Li Yan; Rui Xing; Yi-Jin Kang; Hong-Wei Wang (Rhizosphere, 2025)

Terpenoids from Alpinia galanga and their acetylcholinesterase inhibitory activity - Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Shao-Huan Liu; Xiang-Chun Shen; Nen-Ling Zhang (Natural Product Research, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Inactivation of Cyclotella meneghiniana to prepare biochar by in-liquid pulsed discharge plasma - Yin Li; Yanbin Xin; Bing Sun; Chenxi Man; Emile Mouele; Leslie Petrik; Bernard Jan Bladergroen; Cheng Zhang (Biomass and Bioenergy, 2025)

Alicycliphilus soli sp. nov., Isolated from a Plastic Film Greenhouse Soil and the Proposal for the Reclassification of Diaphorobacter limosus as Alicycliphilus limosus comb. nov. - Xinyu Liu; Hailong Liang; Yingying Liu; Huijun Zhang; Hui Han; Bingyue Xin; Xiaomin Wu; Feng Li; Man Song; Long Zhang (Current Microbiology, 2025)

Electrical Detection of Shale Gas Layers Based on Wide-Field Electromagnetic Method - Li-Xin Man; Zhang-Kun Tan; Jian-Chao Jia; Zhi-Wen Gu; Chang-Heng Yu; Xue-Bo Yin (Applied Geophysics, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Analysis and Control Techniques of Ultra-Shallow Buried Tunnels in Rain-Affected Backfill Soil - Peng-cheng Wang; Li-yang Su; Shu-jie Shang; Xiang-yu Jia; Wei-teng Li; Feng-chuan Jiang; Chun-qing Liu; Xin-jie Man (Geotechnical and Geological Engineering, 2025)

Postharvest fruit rot on blue honeysuckle (Lonicera caerulea L.) caused by Penicillium oxalicum newly reported in China - Haohao Yan; Yuxuan Li; Yusheng Lv; Xin Zhao; Zijian Man; Zexu Chen; Liangchuan Guo; Junwei Huo; Mingyu Sang; Chunyan Li; Hailian Zang; Yi Cheng (Crop Protection, 2025)

Retraction notice to “Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica)” [Chemosphere 352 (2024) 141430] - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2025)

Surface-engineered nanofiltration membranes for sustainable lithium recovery from real brine: Addressing fouling and scaling challenges - Xuesong Li; Man Xu; Xin Liu; Qianhong She; Woei Jye Lau; Linyan Yang (Water Research, 2025)

Unveiling the influence of the Afatg3 gene: Autophagy's role in sporulation, aflatoxin synthesis, pathogenicity, and drug stress response in Aspergillus flavus - Yong-xin Li; Yan Ma; Chao Pan; Linchong Hui; Chan Zhang; Man Liu; Kunlong Yang; Xue Peng; Jun Tian (Food Bioscience, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Diet shift and allometric growth in the early development Odontobutis potamophila - Miao Xiang; Kun Xiao; Hongliang Xu; Bo Li; Hongxi Guo; Zhanhu Yang; Chuankun Zhu; Man Wang; Jie Wang; Wei Xin; Songguang Xie; Xiaoming Zhu; et al. (Aquaculture, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Combined Effects of Cadmium and Lead on Growth Performance and Kidney Function in Broiler Chicken - Man Zhao; Longqiang Xie; Wenbin Huang; Meiling Li; Xin Gu; Wei Zhang; Jintao Wei; Niya Zhang (Biological Trace Element Research, 2025)

Urban estuary serves as a critical nexus for the land-sea transfer of the terrestrial pathogen Toxoplasma gondii - Xin-Kun Zhu; Hany M. Elsheikha; Tao Yang; Man-Yao Li; Wei Cong (Science of The Total Environment, 2024)

Atmosphere-driven oriental regulation of Ru valence for boosting alkaline water electrolysis - Na Xu; Man-Man Li; Hai-Yi Sun; Guodong Li; Xin Wen; Denghao Ouyang; Chun-Ying Liu; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Remediation of AMD based on hydrogeochemical zonation: A typical metal mine in China - Jie Tang; Xin Liu; Bo Li; Yuhan Nie; Xin Gao; Man Gao; Guo Liu (Science of The Total Environment, 2024)

Excitotoxic Storms of Ischemic Stroke: A Non-neuronal Perspective - Xiao-man Yang; Hao Yu; Jia-xin Li; Na Li; Chong Li; Dong-han Xu; Hao Zhang; Tian-he Fang; Shi-jun Wang; Pei-yu Yan; Bing-bing Han (Molecular Neurobiology, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Probing rotaxane dynamics with 19F NMR/MRI: Unveiling the roles of mechanical bond and steric hindrance - Yu Li; Man Luo; Mou Jiang; Rui Zhou; Wanrong Yang; Shenhui Li; Fang Wang; Lijun Zhu; Pei He; Minghui Yang; Xin Zhou; Zhong-Xing Jiang; et al. (Analytica Chimica Acta, 2024)

Berberine improves cognitive impairment by alleviating brain atrophy and promoting white matter reorganization in diabetic db/db mice: a magnetic resonance imaging-based study - Xin-yu Yang; Chun-jing Yang; Xiao-fang Wang; Lei Zhang; Zheng-yuan Shi; De-chun Jiang; Man-zhong Li (Metabolic Brain Disease, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

Prediction of cytochrome P450-mediated bioactivation using machine learning models and in vitro validation - Xin-Man Hu; Yan-Yao Hou; Xin-Ru Teng; Yong Liu; Yu Li; Wei Li; Yan Li; Chun-Zhi Ai (Archives of Toxicology, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

RETRACTED: Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica) - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2024)

VX-765 Alleviates Circadian Rhythm Disorder in a Rodent Model of Traumatic Brain Injury Plus Hemorrhagic Shock and Resuscitation - Yan Li; Yue Xin; Man-Man Qi; Zhi-You Wu; Han Wang; Wei-Chao Zheng; Jie-Xia Wang; Dong-Xue Zhang; Li-Min Zhang (Journal of Neuroimmune Pharmacology, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Porcine β-defensin-2 alleviates aflatoxin B1 induced intestinal mucosal damage via ROS-Erk1/2 signaling pathway - Qinghao Li; Man Zhang; Juan Sun; Yilei Li; Shaopo Zu; Yuqiang Xiang; Xin Jin (Science of The Total Environment, 2023)

One-pot derivatization/extraction coupled with liquid chromatography-tandem mass spectrometry for furfurals determination - Di Chen; Bin Wang; Xin-Li Xu; Xin-Miao Bu; Man-Yu Zhang; Xia Xu; Lei Yu; Nian Shi (Food Chemistry, 2023)

Human dental pulp stem cells have comparable abilities to umbilical cord mesenchymal stem/stromal cells in regulating inflammation and ameliorating hepatic fibrosis - Peixing Chen; Yanchun Lin; Wenbo Lin; Yun Li; Ting Fu; Yuanyue Liu; Tian Guan; Man Xin; Ling Ye; Peiluan Wang; Haoyu Zeng; Kaitao Yao (Human Cell, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

Detection and quantitative analysis of tumor-associated tertiary lymphoid structures - Man Yang; Yurou Che; Kezhen Li; Zengyi Fang; Simin Li; Mei Wang; Yiyao Zhang; Zhu Xu; Liping Luo; Chuan Wu; Xin Lai; Weidong Wang (Journal of Zhejiang University-SCIENCE B, 2023)

The composition characteristics of endophytic communities and their relationship with metabolites profile in Ephedra sinica under wild and cultivated conditions - Hui Zhang; Ye Xia; Jin-Long Cui; Xin Ji; Shuang-Man Miao; Gang Zhang; Yi-Min Li (Environmental Science and Pollution Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Genetic characteristics of a novel HIV-1 recombinant lineage (CRF103_01B) and its prevalence in northern China - Man Dai; Jia Li; Jie Li; Hongyan Lu; Chun Huang; Shiyun Lv; Huihuang Huang; Ruolei Xin (Virus Genes, 2023)

Experimental and numerical investigations on the explosions nearby a free surface from both sides - Hao Tang; Zhao-Li Tian; Xin-Yang Ju; Ji-Tuan Feng; Yun-Long Liu; A-Man Zhang (Ocean Engineering, 2023)

The effects of pulsed electric fields treatment on the structure and physicochemical properties of dialdehyde starch - Ying Li; Jin-Hua Wang; Yu Han; Fu-Hao Yue; Xin-An Zeng; Bo-Ru Chen; Man-Qin Zeng; Meng-Wai Woo; Zhong Han (Food Chemistry, 2023)

Inhibitory effect of cinnamaldehyde on Fusarium solani and its application in postharvest preservation of sweet potato - Chao Pan; Kunlong Yang; Famous Erhunmwunsee; Yong-Xin Li; Man Liu; Shenyuan Pan; Dongjing Yang; Guoquan Lu; Daifu Ma; Jun Tian (Food Chemistry, 2023)

Label-free and selective cholesterol detection based on multilayer functional structure coated fiber fabry-perot interferometer probe - Ruiduo Wang; Minglu Yan; Man Jiang; Yang Li; Xin Kang; Mingxuan Hu; Beibei Liu; Zhengquan He; Depeng Kong (Analytica Chimica Acta, 2023)

Differences in texture and digestive properties of different parts in boiled abalone muscles - Man-Man Yu; Ying-Chen Fan; De-Yang Li; Yu-Xin Liu; Peng-Fei Jiang; Da-Yong Zhou; Bei-Wei Zhu (Food Chemistry, 2023)

Gas hydrate nucleation and growth in a micro-reactor: Effect of individual component separated from the crude oil in the South China Sea - Yu Feng; Man Li; Yuze Han; Qingping Li; Xin Lv; Jiafei Zhao; Lei Yang; Yanzhen Liu; Yongchen Song (Chemical Engineering Journal, 2023)

Asymmetric intramolecular charge transfer enables highly efficient red thermally activated delayed fluorescent emitters - Chao Qu; Huiqin Wang; Yi Man; Zhe Li; Peng Ma; Peng Chang; Xin Li; Chunmiao Han; Yudong Pang; Hui Xu (Chemical Engineering Journal, 2023)

New (4 → 2)-abeo-clerodane diterpenoids from the Polyalthia laui and their chemotaxonomic significance - Zhang-Xin Yu; Xin-Ming Song; Mu-Yuan Li; Man-Man Zhang; Li-Zhu Huang; Xiao-Bao Li (Biochemical Systematics and Ecology, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Damage and Failure Characteristics and Constitutive Model of Copper-Bearing Skarns Disturbed by Hierarchical Dynamic Loading After Loading And Unloading - Chun Wang; Jia Li; Lu- ping Cheng; Xin-ru Li; Pan-long Zhang; Man-gu Hu (Rock Mechanics and Rock Engineering, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

Characteristics and formation mechanism of siltstone-mudstone rhythmic sedimentary sections in the Lower Silurian Longmaxi Formation in the Changning area, South Sichuan Basin, southwest China - Gaoxiang Wang; Lei Chen; Yang Yang; Cui Jing; Man Chen; Xiucheng Tan; Xin Chen; Di Cao; Zibo Wei; Minglong Li; Dong Huang (Frontiers of Earth Science, 2021)

Overexpression of T-type calcium channel Cav3.1 in oral squamous cell carcinoma: association with proliferation and anti-apoptotic activity - Rui-Fang Li; Qi-Wen Man; Jin-Yuan Liu; Yue-Yu Zheng; Xin Gao; Hai-Ming Liu (Journal of Molecular Histology, 2021)

Insights on the Working Principles of Secondary Electrospray Ionization High-Resolution Mass Spectrometry for Quantitative Analysis of Aerosol Chemical Composition - Xin Xu; Jia Fa Zeng; Dan Dan Jin; Zheng Xu Huang; Lei Li; Anthony S. Wexler; Man Nin Chan; Zhen Zhou; Yong Jie Li; Xue Li (Aerosol Science and Engineering, 2021)
Real-time mass spectrometry (MS) has attracted increasing interest in environmental analysis due to its advantages in high time resolution, minimization of sampling artifact, and avoidance of time-consuming sample pretreatment. Among real-time MS methods, secondary electrospray ionization MS (SESI-MS) is showing great promise for the detection of organic compounds in atmospheric particulate matter. In this study, we demonstrated the working principles of secondary nanoelectrospray ionization (Sec-nESI) for real-time measurement of laboratory-generated organic aerosols using l -tartaric acid (TA) as a model compound. Factors affecting the detection of TA particles using a homemade Sec-nESI source coupled with a high-resolution mass spectrometer are systematically investigated. Temperature of ion transport capillary (ITC) was found to be the key factor in determining the ion signal intensity, which shows an increase of intensity by a factor of 100 from ITC temperature of 100–300 °C and could be attributed to more efficient desolvation and ionization. The characteristic fragment ion at m / z 72.99 was selected for quantitative analysis of TA at normalized collision energy of 50%, the optimal value applied during MS/MS analysis. Detection limit of 0.14 µg/m 3 and a linear range of 0.2–2.97 µg/m 3 are achieved. Satisfactory correlations between ion signal intensity and particle surface area ( R 2 = 0.969) and mass concentration ( R 2 = 0.967) were obtained. Although an equally good correlation was observed between signal intensity and particle surface area, the good correlation between signal intensity and particle mass concentration indicates that high solubility of TA ensures efficient dissolution of TA in the primary ESI droplets for further ionization.

Four pairs of proline-containing cyclic dipeptides from Nocardiopsis sp. HT88, an endophytic bacterium of Mallotus nudiflorus L - Wen-Xin Xiang; Qing Liu; Xiao-Man Li; Chun-Hua Lu; Yue-Mao Shen (Natural Product Research, 2020)

Deletion of Type-2 Cannabinoid Receptor Induces Alzheimer’s Disease-Like Tau Pathology and Memory Impairment Through AMPK/GSK3β Pathway - Lin Wang; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Dong-Sheng Sun; Meng-Zhu Li; Fang-Xiao Shi; Man Li; Qing Tian; Jian-Zhi Wang; Xin-Wen Zhou (Molecular Neurobiology, 2018)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

Effects of light intensity on leaf photosynthetic characteristics, chloroplast structure, and alkaloid content of Mahonia bodinieri (Gagnep.) Laferr. - De-Xin Kong; Yan-Qun Li; Man-Lian Wang; Mei Bai; Rong Zou; Hui Tang; Hong Wu (Acta Physiologiae Plantarum, 2016)

Sleep education in Hong Kong - Ngan Yin Chan; Siu Ping Lam; Jihui Zhang; Mandy Wai Man Yu; Shirley Xin Li; Albert Martin Li; Yun Kwok Wing (Sleep and Biological Rhythms, 2016)

OsCML4 improves drought tolerance through scavenging of reactive oxygen species in rice - Xu Ming Yin; Li Fanng Huang; Xin Zhang; Man Ling Wang; Guo Yun Xu; Xin Jie Xia (Journal of Plant Biology, 2015)

Coumarin-containing aminophosphonates bridged with chiral side chain: synthesis and influence of chirality on cytotoxicity and DNA binding - Ya-Jun Li; Man-Yi Ye; Ri-Zhen Huang; Gui-Yang Yao; Ying-Ming Pan; Zhi-Xin Liao; Heng-Shan Wang (Medicinal Chemistry Research, 2014)

Prodrug of green tea epigallocatechin-3-gallate (Pro-EGCG) as a potent anti-angiogenesis agent for endometriosis in mice - Chi Chiu Wang; Hui Xu; Gene Chi Wai Man; Tao Zhang; Kai On Chu; Ching Yan Chu; Jimmy Tin Yan Cheng; Gang Li; Yi Xin He; Ling Qin; Tat San Lau; Joseph Kwong; et al. (Angiogenesis, 2013)

cDNA cloning and characterization of UDP-glucose: anthocyanidin 3-O-glucosyltransferase in Freesia hybrida - Xin Sui; Xiang Gao; Man Ao; Qinmei Wang; Dan Yang; Meng Wang; Yang Fu; Li Wang (Plant Cell Reports, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

In Vitro Micropropagation of Freesia hybrida and the Assessment of Genetic and Epigenetic Stability in Regenerated Plantlets - Xiang Gao; Dan Yang; Donghui Cao; Man Ao; Xin Sui; Qinmei Wang; J. N. Kimatu; Li Wang (Journal of Plant Growth Regulation, 2010)

Phenylpropanoid and flavonoids from osteoprotective fraction of Drynaria fortunei - Xin-Luan Wang; Nai-Li Wang; Hao Gao; Ge Zhang; Ling Qin; Man-Sau Wong; Xin-Sheng Yao (Natural Product Research, 2010)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Sedimentary cycles of trace elements in Salawusu River Valley since 150 ka BP - Yao Chun-xial; Li Bao-sheng; Jin He-ling; David Dian Zhang; Yan Man-cun; Zhu Yi-zhi; Li Hou-xin; Zhang Yu-hong; Luo Kai-li (Journal of Geographical Sciences, 2002)

CaCO3 cycles in salawusu river basin since 150ka B.P. - Kai-li Luo; Bao-sheng Li; Yi-zhi Zhu; He-ling Jin; David Dian Zhang; Man-cun Yan; Hou-xin Li; Chun-xia Yao; Yu-hong Zhang (Chinese Geographical Science, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)